An Integrated Microstructural Study of Dry Snow Metamorphism Under Generalized Thermal Conditions - Miller, Daniel A., II (2002)
Snow microstructure significantly influences the mechanical, thermal, and electromagnetic properties of snow. The microstructure is constantly evolving from the time it is deposited on the surface until it sublimates or melts. The resulting time variant material properties make the study of snow metamorphism of fundamental importance to a wide variety of snow science disciplines. Dry snow metamorphism has traditionally been classified by the thermal gradient encountered in the snowpack. Snow experiencing a predominantly equi-temperature environment develops different micro structure than snow that is subjected to a temperature gradient. As such, previous research has evaluated snow metamorphism based upon select thermal gradient dependent processes, when in reality, there is a continuum of physical processes simultaneously contributing to metamorphism. In previous research, a discrete temperature gradient transition between the two thermal environments has been used to activate separate morphological analyses. The current research focuses on a unifying approach to dry snow metamorphism that is applicable to generalized thermal environments. The movement of heat and mass is not prescribed, but is allowed to develop naturally through modeling of physical processes. Heat conduction, mass conservation, and phase change equations are derived in a simplified two-dimensional approach. Each differential equation is non-linearly coupled to the others through phase change. The microstructural network is then discretized into elements and nodes. Finite difference equations are developed for the network, and numerically solved using iterative techniques. The finite difference model provides a unique platform to study the influence of numerous geometric and thermodynamic parameters relating to dry snow metamorphism. Numerical metamorphism studies in an equi-temperature environment agree well with established trends and published experimental results.